Diet composition in larval fishes of the family Terapontidae (Actinopterygii: Perciformes) in the seagrass-bed of Johor Strait, Malaysia - Arshad, Aziz; Ara, Roushon; Sarker, S. M. Nurul Amin Harmuj Ali; Abd. Ghaffar, Mazlan (Academic Journals, 2013)
Stomach content of fish larvae of family Terapontidae were studied in samples acquired from Merambong Shoal, south western part of Johor, Malaysia from December 2007 to September 2008. Larvae were collected by subsurface towing of a Bongo net. Stomachs were removed from a total of 117 Terapontidae specimens during the study period and the stomach contents were fully examined. Analyses of prey in the stomach showed 24 important food items belonging to six major groups viz., phytoplankton, zooplankton, algae, plant-like matter, debris and unidentified matters. The predominant food items found in the stomach were phytoplankton (74.25%). This was followed by plant matters (8.02%), algae (6.69%), zooplankton (4.95%), debris (3/65%) and unidentified matters (2.45%). Among the food items, phytoplankton was the first rank by simple resultant index (74.25%). Therefore, it could be concluded that the fish larvae of family Terapontidae are mainly herbivorous.